A multiple network-based bioinformatics pipeline for the study of molecular mechanisms in oncological diseases for personalized medicine. Issue 6 (28th May 2021) - Dotolo, Serena; Marabotti, Anna; Rachiglio, Anna Maria; Esposito Abate, Riziero; Benedetto, Marco; Ciardiello, Fortunato; De Luca, Antonella; Normanno, Nicola; Facchiano, Angelo; Tagliaferri, Roberto
Abstract: Motivation: Assessment of genetic mutations is an essential element in the modern era of personalized cancer treatment. Our strategy is focused on 'multiple network analysis' in which we try to improve cancer diagnostics by using biological networks. Genetic alterations in some important hubs or in driver genes such as BRAF and TP53 play a critical role in regulating many important molecular processes. Most of the studies are focused on the analysis of the effects of single mutations, while tumors often carry mutations of multiple driver genes. The aim of this work is to define an innovative bioinformatics pipeline focused on the design and analysis of networks (such as biomedical and molecular networks), in order to: (1) improve the disease diagnosis; (2) identify the patients that could better respond to a given drug treatment; and (3) predict what are the primary and secondary effects of gene mutations involved in human diseases. Results: By using our pipeline based on a multiple network approach, it has been possible to demonstrate and validate what are the joint effects and changes of the molecular profile that occur in patients with metastatic colorectal carcinoma (mCRC) carrying mutations in multiple genes. In this way, we can identify the most suitable drugs for the therapy for the individual patient. This information is useful to improve precision medicine in cancer patients. As an application of our pipeline, the clinically significant case studies of a cohort of mCRC patients with the BRAF V600E-TP53 I195N missense combined mutation were considered. Availability: The procedures used in this paper are part of the Cytoscape Core, available at (www.cytoscape.org ). Data used here on mCRC patients have been published in [55 ]. Supplementary Information: A supplementary file containing a more detailed discussion of this case study and other cases is available at the journal site as Supplementary Data.